Author Correction: Tyrosine dephosphorylated cortactin downregulates contractility at the epithelial zonula adherens through SRGAP1. Issue 1 (December 2017) - Liang, Xuan; Budnar, Srikanth; Gupta, Shafali; Verma, Suzie; Han, Siew-Ping; Hill, Michelle; Daly, Roger; Parton, Robert; Hamilton, Nicholas; Gomez, Guillermo; Yap, Alpha
A correction to this article has been published and is linked from the HTML version of this article.